How much of a socialist legacy? The reemergence of entrepreneurship in the East German transformation to a market economy - Michael Fritsch; Elisabeth Bublitz; Alina Rusakova; Michael Wyrwich (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
The 40 years of socialist regime in East Germany were characterized by a massive anti-entrepreneurship policy. We investigate the reemergence of entrepreneurship in East Germany during its transformation to a market economy following the collapse of the East German state in 1989. It took about 15 years until self-employment levels in East Germany reached those of West Germany. Despite this catch up, we find a number of peculiarities in East German self-employment that appear to be a continuing legacy of the socialist period. In particular, older and better-educated East Germans have a relatively low propensity for starting an own business. Moreover, East German workers tend to have a lower variety of skills than their West German counterparts, which could explain a lower propensity for start up in the early years after reunification. Despite this socialist imprint, we also find considerable continuity in the levels of self-employment in the 1920s and those after transition to a market economy, suggesting the existence of a long-lasting regional entrepreneurship culture.
Keywords: L26; O11; 330; Entrepreneurship; self-employment; new business formation; transformation; East Germany; Unternehmer; Selbstständige; Unternehmensgründung; Wirtschaftliche Anpassung; Neue Bundesländer; Unternehmer; Wirtschaftskultur; DDR